Evaluasi Atas Perhitungan Harga Pokok Produksi Dalam Kaitannya Untuk Menentukan Harga Jual. Studi Kasus Pada CV. Jawara Karsa Agusto - Pramiudi, Udi; Zesica, Reyna (Institut Bisnis dan Informatika Kesatuan, 2016)
Production cost of goods sold is often made as a guidance by management to make decisions on future activities in order to achieve company’s objectives, mainly the number of profit intended to gain. This research is aimed at discovering how production cost of goods sold is affecting the selling price. CV. Jawara Karsa Agusto is a manufacturing company running in food industry, especially bread making. The company does not have certain standard to decide the selling price, rather fluctuating and following the market’s progress. The results show that production cost of good sold is affecting the decision of selling price. Management should also consider the rising in raw materials’ prices when making policies such as production cost efficiency, thus the company’s targeted profit will still be achieved.